2012
DOI: 10.2220/biomedres.33.249
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia in Ednrb-deficient rat was strongly modified by genetic background

Abstract: The endothelin signaling pathway plays an important role in the migration, proliferation, and differentiation of neural crest cells. Mutations in the gene encoding the endothelin receptor type B (EDNRB) cause three symptoms: aganglionosis, pigmented disorder and hearing loss. In addition, the Ednrb null mice show abnormal splenic microarchitecture with lymphopenia. In this study, we examined whether similar phenotypes are reproduced in three Ednrb-null rat strains that we established previously. AGH-Ednrb sl/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Recently, Dang et al reported that the AGH-Ednrb sl/sl rat model of HSCR showed lymphoid depletion with markedly reduced spleen weight and total splenic cell count of less than 15% of wild-type AGH rats, with severe reduction of B cells, and CD4 and CD8 T cells [29]. The AGH-Ednrb sl/sl rat also had significantly reduced thymic weight and cell number, with no change in the CD4/CD8 ratio when studied at only 8 days of life, but otherwise very similar to the murine models in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dang et al reported that the AGH-Ednrb sl/sl rat model of HSCR showed lymphoid depletion with markedly reduced spleen weight and total splenic cell count of less than 15% of wild-type AGH rats, with severe reduction of B cells, and CD4 and CD8 T cells [29]. The AGH-Ednrb sl/sl rat also had significantly reduced thymic weight and cell number, with no change in the CD4/CD8 ratio when studied at only 8 days of life, but otherwise very similar to the murine models in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 54 ] However, Dang et al . [ 55 ] found that genetic background was related to different immune state. Abnormal splenic microarchitecture with lymphopenia was observed in AGH-Ednrb−/− rats, but not detected in LE and F344 genetic background Ednrb−/− rats.…”
Section: Mmune F Unctionmentioning
confidence: 99%
“…Additionally, small splenic size has been noted in the conventional EdnrB deletion model1724. Based on this, we hypothesized that there may be a direct contribution of NCC to the spleen.…”
Section: Resultsmentioning
confidence: 90%